Disseminated herpes zoster and some other infections may navigated to newly-diagnosed human immunodeficiency virus infection - Wiryandari, Ni Putu Nita; Suryana, Ketut (International Journal of Research in Medical Sciences, 2022)
Almost half of the human immunodeficiency virus (HIV)-positive patients are late diagnosed, which is always associated with higher mortality and morbidity due to various opportunistic infections (OI). Thus, recognition of HIV indicator conditions is important for HIV screening. Cluster of differentiation 4 (CD4) counts <200 cells/mm3 are at the highest risk of herpes zoster-related complications, including disseminated herpes zoster (HZ). Oral candidiasis (OC) is a clinical predictor of HIV infection progression. Here we report a 52-year-old female presented with grouped vesicles with bulla on dermatome L2-L4 sinistra and multiple scattering erythematous vesicular rashes on the whole body. White patches on the tongue with painful swallowing and progressive shortness of breath, cough, low-grade fever, and night sweats. She had an unintentional weight loss of 15 kg. Chest radiograph showed infiltrates in the left lung and right para hilar and paracardial fields, negative Xpert MTB/RIF, and patient newly diagnosed with advanced HIV infection (reactive result on provider initiative test and counseling (PITC) with CD4 level was 8 cell/ml). The patient showed improvement after early treatment with antiviral, antifungal, antimicrobial, first-line fixed-dose combination (FDC) tuberculosis, and prophylactic antibiotic.